Papillary sclerosing thyroid carcinoma: Diffuse sclerosing variety. About a case - Maggiolo, José F; Chiossoni, Marta; Bowley, Hilmer; Almeida, Edgardo; Lara, Elisa; Bergalli, Luis; Navarrete, Héctor (Cirugía del Uruguay, 1994)
We report a distinctive variant of thiroid papillary carcinoma designated as "Diffuse Sclerosing Papillary Carcinoma", this lesion is characterized by clinical and morphologic aspects. The practica/ importance of the recognition of this variant of papillary carcinoma lies in the more aggresive therapeutic approach that might be needes to eradicate it and the bad prognosis it has if we compare it with the conventional papillary carcinoma.